2009
DOI: 10.1111/j.1365-3083.2009.02247.x
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ and CD8+ Distribution Profile in Individuals Infected by Schistosoma mansoni

Abstract: Rationale: Patients with chronic Schistosoma mansoni infection show lower anti‐soluble egg antigen (SEA) proliferation responses and higher responses to soluble worm antigen preparation (SWAP). Objective: To compare the activation status and proliferation response of peripheral blood mononuclear cells (PBMC) of infected (XTO) and egg‐negative individuals (NI) living in the same endemic area. Methods: XTO (n = 51) and NI individuals from the same geographical area (n = 37) and healthy blood donors (n = 22) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In a previous study [24], an increase in HLA-DR expression was observed on CD8 + T cells without in vitro stimulation. However, when we evaluated the expression of activation markers in the NI and XTO groups after SEA and SWAP stimulation, (Figure 1) there was no increase of any marker compared to the BD group.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a previous study [24], an increase in HLA-DR expression was observed on CD8 + T cells without in vitro stimulation. However, when we evaluated the expression of activation markers in the NI and XTO groups after SEA and SWAP stimulation, (Figure 1) there was no increase of any marker compared to the BD group.…”
Section: Discussionmentioning
confidence: 90%
“…In patients during the chronic intestinal phase of schistosomiasis, cell proliferation is reduced in SEA-stimulated PBMCs compared to uninfected individuals [3]. Our previous findings [24] showed no difference between T cell proliferation in the XTO, NI and BD groups after both SEA and SWAP stimulation. However, the proliferation profile in this study is consistent with the findings of most other studies [3,4,27,28] that show lower CD4 + and CD8 + T cell proliferation in the XTO group than the BD group after SEA stimulation (Figure 2C and 2D).…”
Section: Discussionmentioning
confidence: 96%
“…Studies developed by Pancré et al [49] in murine model demonstrated that SEA was able to stimulate IFN- γ or IL-2 producing CD8 + T cells, suggesting a type 1 response induced by SEA. In humans, Oliveira-Prado et al [50] showed a smaller percent of CD4 + and a higher percent of CD8 + cells in peripheral blood from patients with chronic schistosomiasis. Moreover, our group has previously described the putative role of CD8 + T subsets in controlling morbidity during human schistosomiasis, which was evidenced by the increased levels of activated HLA-DR + CD8 + T lymphocytes in patients presenting intestinal clinical form (INT) of the disease and low levels of CD28 + CD8 + cells in hepatosplenic patients [5153].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of this understandable criticism, our longitudinal childhood cohort study was able to demonstrate remarkable differences in CD8 + T cell subsets associated with prolonged pathogen exposure, notably to malaria and Schistosomiasis. The role of Schistosomiasis in shaping human T cell lineage and fate decisions is speculative at this stage, but Schistosomiasis has been shown to activate CD8 + T cells (50). Additionally, the distinctive plasma composition observed in the Kisumu compared with the Nandi children displays another layer of complexity generally overlooked in human immunology studies.…”
Section: Consistent With Our Findings Are Reports That Cd8mentioning
confidence: 97%